The Effectiveness of Aromatherapy on Pain Intensity in First Stage Mothers at TPMB Ana Masnah, Tarumajaya Bekasi - Ida Hidayati (LPPM Universitas Muhammadiyah Tasikmalaya, 2024)
During the labor process, most women will feel pain. During childbirth, pain is a sign that the cervix is open and enlarged. However, the pain that occurs will have a bad impact on the mother and baby if not handled properly. The aim of this community service is to determine the effectiveness of aromatherapy on the intensity of pain in postpartum mothers in the first stage at TPMB Ana Masnah, Tarumajaya Bekasi in 2024. This community service used quasi experimental with a total sampling with a sample of 20 people. Data techniques include uivariate analysis using frequency distributions and bivariate analysis using statistical calculations. Based on the community service results, it was found that the average age of postpartum mothers in the first stage was of productive age. After being given treatment there was a reduction in pain in mothers in the first stage of birth, thus proving the effectiveness of Aromatherapy on the intensity of pain in mothers in the first stage of birth at TPMB Ana Masnah Tarumajaya Bekasi in 2024. The conclusion from the results of this community service is that there is effectiveness of Aromatherapy on the intensity of pain in first-stage mothers at TPMB Ana Masnah Tarumajaya Bekasi in 2024. Suggestions for providing information about the benefits of aromatherapy to reduce pain. felt in mothers in the first stage.